Functional and conservation-related traits of bird communities in tropical restoration and second-growth forest patches - Gussoni, Carlos O. A. (2024)
Forest restoration is an important strategy to recover biodiversity in degraded areas, though we know much more about its importance to the recovery of the vegetation than the associated animals and their ecological functions. We surveyed with 10-min point counts the bird communities in 12 natural forest fragments (0.6–79.0 ha) and nine restoration areas (5–60 years old, 8.3–305 ha) in a region of severe forest conversion in the Brazilian Atlantic Forest, focusing on the ecological functions performed by birds related to diet and foraging stratum, as well as traits pertinent to their conservation (capacity to cross open areas, sensitivity to forest disturbance, forest dependence, migratory status). Taking into account the potential confounding effects of the size of sampled areas, we tested for differences between forest fragments and restoration areas in the species richness and abundance of birds according to their functional and conservation-related traits. While the species richness of most of the trait-based bird groups did not differ between the two vegetation types, most of them had greater abundances in forest fragments. In general, some of the groups of greater conservation concern (e.g., birds with low capacity to cross open areas) had greater species richness in forest fragments, while the abundances of groups generally more resistant to forest disturbance (e.g., granivores, omnivores, non-forest birds) did not differ between vegetation types. We showed that although the species richness of bird groups defined by functional and conservation-related traits occurring in restoration areas were similar to forest fragments, their abundances were in general lower in restoration areas, except for groups that are more resilient to habitat disturbance and, therefore, of least conservation concern. But we also highlight that, except for the most sensitive species, restoration areas are serving as habitat for many forest bird species in landscapes dominated by sugar cane monocultures and pasturelands, which by itself lend importance to such areas.